Handbook on Quality and Standardisation in E-Learning - Ehlers, Ulf-Daniel.; Pawlowski, Jan Martin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Quality and standardisation in e-learning have become crucial success factors for organisations in learning, education and training: E-Learning has changed from an ‘early adopter’ stage to an integrated part of learning scenarios leading to major changes in educational organisations towards quality orientation. For building a knowledge society, it is critically important to thoroughly understand quality and standards in e-learning. The handbook provides a cross-national perspective on these issues and draws a clear picture of the situation in quality development and standardisation. It covers topics of a rather foundational nature in quality and standardisation research as well as descriptions of quality approaches, instruments, standards, experiences and best practices. The Handbook is directed to learners, professionals, researchers and policy makers – people creating the next generation of learning.
Quality in European e-learning: An introduction -- Quality in European e-learning: An introduction -- Quality in a Europe of diverse systems and shared goals -- Quality in a Europe of diverse systems and shared goals -- European quality development: Methods and approaches -- Quality of e-learning: Negotiating a strategy, implementing a policy -- The maze of accreditation in European higher education -- Adopting quality standards for education and e-learning -- Process-oriented quality management -- An analysis of international quality management approaches in e-learning: Different paths, similar pursuits -- The quality mark e-learning: Developing process- and product-oriented quality -- Competency-based quality securing of e-learning (CQ-E) -- Quality of e-learning products -- Quality evaluation for e-learning in Europe -- Towards a model for structuring diversity: Classifying & finding quality approaches with the EQO model -- E-learning standards -- The standards jungle: Which standard for which purpose? -- Architectures and frameworks -- Content and management standards: LOM, SCORM and Content Packaging -- Educational interoperability standards: IMS learning design and DIN didactical object model -- Developing and handling learner profiles for European learner information systems -- Improving European employability with the e-portfolio -- Interface standards: Integration of learning and business information systems -- Facilitating learning objects reusability in different accessibility settings -- Out of the past and into the future: Standards for technology enhanced learning -- Fields of practice and case studies -- Organisational and cultural similarities and differences in implementing quality in e-learning in Europe’s higher education -- Rethinking quality for building a learning society -- Myths and realities in learner oriented e-learning-quality -- The e-learning path model: A specific quality approach to satisfy the needs of customers in e-learning -- Pedagogic quality — supporting the next UK generation of e-learning -- Quality in cross national business models for technology based educational services -- E-learning quality and standards from a business perspective -- A framework for quality of learning resources -- LearnRank: Towards a real quality measure for learning -- Quality of e-learning in tertiary education: Managing a balance between divergence and convergence -- Best practices for e-learning.
Keywords: Business mathematics; Information technology; Business—Data processing; Educational technology; Education—Data processing; Business Mathematics; IT in Business; Educational Technology; Computers and Education